ORGANIZATION OF EARLY DIAGNOSIS AND PREVENTION OF PYELONEPHRITIS IN CHILDREN (World Bulletin of Public Health, 2023)
Pyelonephritis is a bacterial infection that affects the kidneys, which is one of the most common bacterial infections in children. The infection may affect one or both kidneys and can lead to severe complications if not detected and treated early. Early diagnosis and prevention of pyelonephritis is essential to avoid complications and ensure the health and well-being of children. This article discusses the organization of early diagnosis and prevention of pyelonephritis in children